SELECTED FACTORS AND PRICES OF COMMERCIAL REAL ESTATE IN NAKURU TOWN EAST SUB COUNTY, KENYA - KIBOR, TANUI MIKE (My University, 2024)
The prices of commercial properties in Nakuru have fluctuated in recent years. In 2018, the prices of commercial properties in Nakuru declined by an average of 2.7%, with the retail sector being the hardest hit, registering a decline of 4.4%. Therefore, this study sought to assess the effect of selected factors on the prices of commercial real estate in Nakuru Town East Sub County. Specifically, the study focused on the effect of interest rates on the prices of commercial real estate, the effect of employment rates, demographics, and availability of credit on the prices of commercial real estate in Nakuru Town East Sub County. The study was anchored on the classical theory, credit channel theory, and life cycle theory. The study adopted an explanatory research design. The study targeted operational managers and financial managers from 60 reals estate agents and companies in Nakuru Town East Sub County. A census design was adopted. A questionnaire was used to collect primary data. A pilot-test was conducted in Nakuru West Sub-County. Content and face validity were enhanced. Internal consistency technique was adopted with Cronbach’s Alpha to measure reliability. Quantitative data was analyzed by Statistical Package for Social Sciences. Descriptive and inferential statistics were employed in the study. The analyzed data was presented in the form of tables. Based on the findings the study concluded that there is a positive and statistically significant correlation between interest rates on prices of commercial real estate in Nakuru Town East Sub County (r=0.607; p<0.05). In addition, the study concluded that there is a positive and statistically significant correlation between employment rate on prices of commercial real estate in Nakuru Town East Sub County (r=0.712; p<0.05). Furthermore, the study concluded that there is a strong positive correlation between demographics on prices of commercial real estate in Nakuru Town East Sub County (r=0.828; p<0.05). Finally, the study concluded that a strong positive correlation existed between the availability of credit on prices of commercial real estate in Nakuru Town East Sub County (r=0.800; p<0.05). Regarding the effect of interest rates on prices of commercial real estate, the researcher recommended that commercial real estate should monitor central bank rate decisions to stay informed about central bank rate decisions as they can influence overall market sentiment and risk appetite. Based on the effect of the employment rate of commercial real estate, the researcher recommended that commercial real estate should assess labor force participation rates. Moreover, regarding the effect of demographics on the prices of commercial real estate, the researcher recommended that commercial real estate should adapt to changing housing demands. Further, regarding the effect of the availability of credit on the prices of commercial real estate, the researcher recommended that commercial real estate should stay informed on credit spreads
Keywords: Interest Rates; Employment Rate; Demographics; Availability of Credit; Prices of Commercial Real Estate